The Implementation of Hiradc Method in Computer Laboratory - M. Affan Mahfudz1, Putri Ayuni Alayyannur1, Dani Nasirul Haqi1, Abdul Rohim Tualeka1, Fauziah Mukti (Indian Journal of Forensic Medicine & Toxicology, 2020)
The computer laboratory of the Faculty of Public Health, Universitas Airlangga is used as a research site, measurement or scientific training for about 15,000 students. There are various types of activities which are at high risk, especially in the use of electricity, which can cause short-circuit and leads to fire. The objective of this study was to apply the Hazard Identification, Risk Assessment and Determining Control (HIRADC) methods in the computer laboratory as an effort to prevent occupational accidents and illness of the user. This study was an observational research using cross sectional design. The observation was conducted on the source of hazard and control efforts on the computer laboratory. Interview was conducted on the lecturers and administrative staff who are in charge of the computer laboratory. The results of the hazard identification indicated that there were 17 hazard sources that can cause 18 risks. Based on the risk assessment conducted on a activities practicum, there are 18 risks classified into 2 risk levels, those are 3 risks with moderate risk level and 15 risks with low risk level. The three level of moderate risks include taking off the shoes in standing position which can cause sprains, there is no first aid box and using electric current which can cause short circuit, electric shock and fire risk. The control that can be carried out by management laboratory to reduce the three moderate risk are by giving advice to taking off the shoes in sitting position, covering the socket which has risky placement by using duct tape to avoid the risk of electric shock as well as the provision of a light fire extinguisher for fire risk and the last providing first aid kits to treat the accidents that occur in the laboratory as soon as possible.